Preserving National Identity Through a Socio-Cultural Ecosystem: The Indonesian Diaspora in Johor Bahru - S. Bekti Istiyanto; Munadhil Abdul Muqsith; Fitria Ayuningtyas; Gustiana Sabarina (International Journal of Asia Pacific Studies, 2026)
In the Asia-Pacific region, intensified cross-border mobility has reshaped how national identity is experienced and sustained among diaspora communities, particularly in culturally proximate yet politically differentiated contexts. This study examines how the Indonesian diaspora in Johor Bahru, Malaysia, preserves Bangsa Indonesia within everyday transnational life, moving beyond cultural symbolism to foreground the relational and institutional conditions that enable identity continuity. Employing a qualitative case study design, this study draws on in-depth semi-structured interviews with five purposively selected Indonesian migrant workers and students. Data were analysed using a thematic approach. The results demonstrate that national identity preservation operates through a socio-cultural ecosystem comprising three interdependent pillars: (1) diaspora communities as cultural fortresses that sustain identity through ritualised practices and regional heritage; (2) community networks as social safety nets that provide emotional, material, and moral security; and (3) institutional scaffolding provided by the Indonesian Consulate and host universities, which confers legitimacy, resources, and public visibility. These mechanisms function unevenly across diaspora positions: migrant workers predominantly mobilise bonding social capital oriented towards survival and solidarity. At the same time, students activate bridging and linking capital to perform national identity through cultural diplomacy and institutional engagement. This study contributes to Asia-Pacific diaspora scholarship by conceptualising national identity preservation as an ecosystemic, stratified, and institutionally mediated process rather than a passive or homogeneous attachment. By integrating diaspora identity theory with social capital analysis, this study offers a transferable analytical framework for examining identity, power, and belonging across regional migration corridors.